O limiar em disputa: a produção do espaço litorâneo de Salvador (BA) - Janaína Lisiak (2020)
Urban spatial production in Salvador (Bahia) is the object of research, which is tested on its coast. The collation of data for the construction of present reflective analysis takes place under an experimental and exploratory methodological perspective, whose empiricism occurs through the presence in the urban space. Thus, we seek to give visibility to different scales, bringing, above all, the speeches about those territories that hardly circulate. We will approach aspects of the city in their daily lives, around Pedra Furada and its surroundings, where different agents coexist and dispute the production of space as an expression of the various interests involved. At the global level, since the end of the 20th century, there has been an increase in public works, mobilized by public management, to attract and strengthen economic circuits, especially tourism. Such operations commonly ignore the social dynamics existing in the territories, reaching, in certain cases, their disarticulation. However, when observing the city on a daily basis, practices reveal social fabric that, in the case of Pedra Furada, indicates the relationship of the city with the sea as a component of the urban condition of Salvador.